Values of Islamic Teaching in Candung Kawik Folklore - Sri Nur Sari; Slamet Subiyantoro; Kundharu S. (UIN Maulana Malik Ibrahim Malang, 2020)
Folklore is part of the community. So that there is no extinction then done as documentation such as folklore Candung Kawik who came from Lampung. Folklore is currently less desirable and does not have a place from the community; therefore, the research is done so that the story still exists. The purpose of this study is to describe the values of Islamic teachings contained in Candung Kawik folklore. The method used to find the values of Islamic teachings is a descriptive qualitative method with content analysis. The primary data source in this study is Lampung folklore. The technique of data collection is done by literature study and recording. The result showed that there were eight values of Islamic teachings, namely faith, Islam, ihsan, taqwa, sincerity, trust, gratitude, and patience. All the values of Islamic education are obtained from the learning and actions of the characters in the story and can be used as learning material.Cerita rakyat merupakan bagian dari kebudayaan masyarakat. Agar kebudayaan tidak punah maka dilakuakn suatu pendokumentasian seperti cerita rakyat Candung Kawik yang berasal dari Lampung. Cerita rakyat sekarang ini kurang diminati dan tidak mendapatkan tempat dari masyarakat, oleh karena itu dilakukan penelitian agar ceritanya masih ada. Tujuan dari penelitian ini untuk mendeskripsikan nilai-nilai ajaran Islam yang terdapat dalam cerita rakyat Candung Kawik. Metode yang digunakan untuk menemukan nilai-nilai ajaran Islam adalah metode kualitatif deskriptif dengan analisis isi. Sumber data primer dalam penelitian ini adalah cerita rakyat Lampung. Teknik pengumpulan data dilakukan dengan studi pustaka dan pencatatan. Hasil penelitian menunjukan ada delapan nilai-nilai ajaran Islam yaitu iman, islam, ihsan, taqwa, ikhlas, tawakal, syukur, dan sabar. Semua nilai-nilai pendidikan Islam didapat dari perilaku dan perbuatan para tokoh di dalam cerita dan dapat dijadikan bahan pembelajaran.